Openness and Technological Innovation in East Asia : Have They Increased the Demand for Skills? - Almeida, Rita K. (2012)
This paper examines whether the increased openness and technological innovation in East Asia have contributed to an increased demand for skills in the region. The author explores a unique firm level data set across eight countries in Asia and the Pacific region. The results strongly support the idea that greater openness and technological innovation have increased the demand for skills, especially in middle-income countries. In particular, while the presence in international markets has been skill enhancing for most middle-income countries, this is not the case for manufacturing firms operating in China and in low-income countries. The author interprets this to support the premise that if international integration in the region continues to intensify and technology continues to be skilled biased, policies aimed at mitigating the skills shortages should produce continual and persistent increase in skills.